2020
DOI: 10.1088/2058-6272/ab988a
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage γ ray emission via ultrahigh intensity laser pulse interaction with a laser wakefield accelerated electron beam

Abstract: In this study, we investigate the generation of twin γ ray beams in the collision of an ultrahigh intensity laser pulse with a laser wakefield accelerated electron beam using a particle-in-cell simulation. We consider the composed target of a homogeneous underdense preplasma in front of an ultrathin solid foil. The electrons in the preplasma are trapped and accelerated by the wakefield. When the laser pulse is reflected by the thin solid foil, the wakefield accelerated electrons continue to move forward and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The laserplasma accelerators are an alternative way to generate highenergy X-and γ-rays [9][10][11][12] by synchrotron radiation [13,14], bremsstrahlung [15,16], and nonlinear Compton scattering [17][18][19][20][21][22] processes. Accordingly, recent studies involving both theory and experiments have shown that energetic, collimated, and brilliant γ-rays can be obtained by an all-optical method by intense laser interaction with plasmas [23][24][25][26][27][28][29]. However, most of them do not include the γ beam orbital angular momentum (OAM), which also has potential application in many areas.…”
Section: Introductionmentioning
confidence: 99%
“…The laserplasma accelerators are an alternative way to generate highenergy X-and γ-rays [9][10][11][12] by synchrotron radiation [13,14], bremsstrahlung [15,16], and nonlinear Compton scattering [17][18][19][20][21][22] processes. Accordingly, recent studies involving both theory and experiments have shown that energetic, collimated, and brilliant γ-rays can be obtained by an all-optical method by intense laser interaction with plasmas [23][24][25][26][27][28][29]. However, most of them do not include the γ beam orbital angular momentum (OAM), which also has potential application in many areas.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we investigated an efficient method of generating high-energy γ-photons using the interaction between a wakefield-accelerated electron beam and a counter-propagating high-intensity laser pulse with a compound target, and obtained two groups of γ-rays with a small divergence angle. [31] Chang et al [32] proposed a new resonance acceleration scheme for generating relativistic electron bunches and brilliant γ-rays, used a three-dimensional particle-in-cell (PIC) simulation and reported γ-ray pulses with a peak brilliance of 10 25 photons/s/mm 2 /mrad 2 /0.1%BW (15 MeV) at a laser intensity of 1.9 × 10 23 W/cm 2 . More recently, Zhang et al [33] reported nano-micro array thin target for ultra-short (440 as) and ultra-bright [10 24 photons/s/mm 2 /mrad 2 /0.1%BW (15 MeV)] γ-ray emission with high conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have indicated that ultrahighintensity laser-plasma interaction could trigger the processes of γ photon emission and electron-positron pair production [10,11,[18][19][20][21][22][23]. Various mechanisms have been proposed [24][25][26][27][28] and, simultaneously, considerable theoretical and numerical studies have been undertaken to provide detailed physical explanations for these QED processes [5][6][7][8][9][10][11][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. If the generation process of the γ photon can be triggered, it will produce a dense beam of positrons in the laboratory, which will facilitate several new fields of research [12,14,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%